Clinical Features Associated with Frozen Shoulder Syndrome in Parkinson’s Disease - Ya-Ting Chang; Wen-Neng Chang; Nai-Wen Tsai; Kuei-Yueh Cheng; Chih-Cheng Huang; Chia-Te Kung; Yu-Jih Su; Wei-Che Lin; Ben-Chung Cheng; Chih-Min Su; Yi-Fang Chiang; Cheng-Hsien Lu (Parkinson's Disease)
Background. Frozen shoulder syndrome is a common musculoskeletal disease of idiopathic Parkinson’s disease (PD) that causes long-term pain and physical disability. A better understanding of the associated factors can help identify PD patients who will require prevention to improve their quality of life. Methodology. This prospective study evaluated 60 shoulders of 30 PD patients. Correlation analysis was used to evaluate the relationships between clinical factors and shoulder sonography findings. Results. Frozen shoulder syndrome was found in 14 of 30 PD patients affecting 19 shoulders, including bilateral involvement in five and unilateral involvement in nine. There was a significant positive correlation between the parameters of sonography findings and frozen shoulder syndrome (i.e., thickness of bicipital effusion and tendon thickness of the subscapularis and supraspinatus) and mean ipsilateral Unified Parkinson’s Disease Rating Scale (UPDRS) III and its subscores (tremor, rigidity, and bradykinesia scores). Conclusions. Higher ipsilateral UPDRS and subscores are associated with increased effusion around the biceps tendon, with increased tendon thickness of subscapularis and supraspinatus. Preventing frozen shoulder syndrome in the high-risk PD group is an important safety issue and highly relevant for their quality of life.